2018
DOI: 10.15376/biores.13.3.6300-6320
|View full text |Cite
|
Sign up to set email alerts
|

How to manage careers in Slovak small and medium-sized wood-processing enterprises

Abstract: Current approaches to human resource management are focused on the sustainable development of small and medium-sized enterprises (SMEs). Career strategies of employees are its integral part. The aim of this paper is to determine the changes in professional priorities of employees in small and medium-sized wood-processing enterprises in the area of motivation relating to career aspiration throughout the course of life. The research outcomes show significant correlation between age, gender, and motivation factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…In terms of age, significant differences appear in the case of women up to 30 years old (opportunity for climbing the corporate ladder for single women), in the case of men aged 40 and 50 (this is the age for men to build the career) and in the case of women aged up to 50 (their children adult and women can build their career). Similar to our findings, Hitka et al (2018Hitka et al ( , 2021 show a sig-nificant correlation between age, gender, education and motivation factors relating to career aspiration.…”
Section: Resultssupporting
confidence: 91%
“…In terms of age, significant differences appear in the case of women up to 30 years old (opportunity for climbing the corporate ladder for single women), in the case of men aged 40 and 50 (this is the age for men to build the career) and in the case of women aged up to 50 (their children adult and women can build their career). Similar to our findings, Hitka et al (2018Hitka et al ( , 2021 show a sig-nificant correlation between age, gender, education and motivation factors relating to career aspiration.…”
Section: Resultssupporting
confidence: 91%
“…Trading enterprises use personnel controlling to a lower extent compared to manufacturing enterprises and service enterprises. According to the authors (Hitka et al, 2007(Hitka et al, , 2018, employees must be adequately motivated and willing to work for the enterprise, as large enterprises do not prefer a family atmosphere as in the case of small enterprises. The results showed that large enterprises are often more advanced in thinking and understanding the use of controlling and its individual subsystems.…”
Section: Resultsmentioning
confidence: 99%
“…The reason is the lack of interest of Slovak enterprises in this part of controlling. As the authors agree (Sedliačiková et al, 2012(Sedliačiková et al, , 2019Hitka et al, 2018;Osmanagić-Bedenik, 2015), personnel controlling is part of cost controlling, where it can be included.…”
Section: Cost Controllingmentioning
confidence: 90%
See 1 more Smart Citation
“…It was found that the differentiation of profitability of enterprises in section H in individual voivodeships depends mainly on financial management. Operational management affects this differentiation only in terms of sales profitability decisions (Hitka et al, 2018). The tax ordinance had no major impact on the changes in the ROE differences.…”
Section: Introductionmentioning
confidence: 95%